EFFECT OF ALENDRONATE ON THE HEALING TIME OF DISTAL RADIAL FRACTURES TREATED CONSERVATIVELY: AN OBSERVATIONAL STUDY - Koshy, Nidhin; Pinto, Deepak; Sujir, Premjit; Joe, Varghese; Kamath K, Ghanashyam (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: Although fragility fractures of the distal radius are common, osteoporosis treatment requires exploration as attempts to improve postfracture investigations have been only partially successful. Bisphosphonates may help minimize the risk of secondary fractures but being a potent antiresorptive agent; it raises concerns about adverse effects on the healing process. This observational study examines the effect of bisphosphonate (alendronate) on healing of acute fractures of distal radius through 66 patients aged >45 years admitted to two tertiary care hospitals in Mangalore from May 2014 to September 2016. Methods: The methodology consists of purposive sampling from two groups: Control having 33 patients not on alendronate therapy and cases comprising 33 who are on alendronate as part of prophylaxis for osteoporosis before fracture occurrence, with outpatient reviews at 2-week intervals starting from the 6th till fracture union seen. At each visit, plain radiographs of the involved wrist were taken to yield time to cortical bridging, with range of active movement of the affected wrist taken using a goniometer. Data were analyzed using Statistical Package for the Social Sciences software version 17.0 for t values, p values and correlations and results were presented in the form of graphs and tables. Results: No significant differences were observed in the groups (as per p values) w.r.t. gender (0.804), age (0.835), time to healing (1.000), dorsiflexion (0.956), palmar flexion (0.670), ulnar deviation (0.441), radial deviation (1.000), supination (0.132), or pronation (0.302). Quick Disabilities of the Arm, Shoulder and Hand score did not differ by >95% between the groups over the analysis period. Conclusion: It was observed that alendronate administration in distal radius fractures did not appear to delay fracture healing times radiologically or clinically.